Analysis of the performance profile of the NCERD thermosyphon solar water heater - Solomon Agbo (Journal of Energy in Southern Africa, 2017)
The work reported here is the performance profile of a thermosyphon solar water heater developed by the National Centre for Energy Research and Development (NCERD), University of Nigeria, Nsukka. The performance evaluation was based on the mathematical models that describe the test system and some measured experimental data. The effect of some of the design and operating parameters that have been shown to affect the system’s performance was investigated. The parameters considered included the number of glazing covers, glazing cover thickness, tube spacing and the nature of absorber plate material. The performance results indicate that the test system has a maximum average daily collector efficiency of 0.658 and a mean system temperature of 81oC. The efficiency of the collector drops to an average seasonal value of 0.54 with a negligible variation across the three climatic seasons was covered in the study. With a tube spacing not exceeding 10 cm, the performance of the system is optimized irrespective of the nature of the absorber plate material. We found that the number of glazing covers affects the top-loss coefficient of the system depending on the type of absorber plate used. Multiple glazing shows a negligible contribution especially for low temperature application. The glazing cover thickness does not affect the performance of the system significantly.